Antidiabetic and Antilipidemic Effect of Musa balbisiana Root Extract: A Potent Agent for Glucose Homeostasis in Streptozotocin-Induced Diabetic Rat - Kalita, Himadri; Boruah, Dulal C.; Deori, Meetali; Hazarika, Ankita; Sarma, Rahul; Kumari, Sima; Kandimalla, Raghuram; Kotoky, Jibon; Devi, Rajlakshmi (Frontiers in Pharmacology, 2016)
Folklore studies have revealed that Musa balbisiana Colla (MB) (Family: Musaceae) has high medicinal properties. The purpose of the present study is to evaluate antihyperglycemic, and antioxidant activity of MB extracts in streptozotocin (STZ) induced diabetic rats. In vitro antioxidant and antidiabetic activity of MB extracts i.e. root extract ( RE), shoot extract (SE) and inflorescence extract (IE) were determined by using various methods viz 1,-1-diphenyl-2-picrylhydrazyl (DPPH) and a method to assess their possible effect on glucose diffusion across gastrointestinal tract and identify bioactive compound of potent extract. In vivo antilipidemic and antidiabetic activity was evaluated by administrating oral dose of RE for 15 days on STZ- induced diabetic rat. RE showed highest antioxidant activity by scavenging DPPH radical (IC50 32.96µg/ml) and inhibit 30% glucose movement in vitro. The methanol extract of root showed the presence of calyx [4] arene category of the compound. Furthermore, RE treated rat revealed a reduction in fasting blood glucose (62.5%), serum total cholesterol (36.2%), triglyceride (54.5%) and low-density lipoprotein (50.94%) after 15 days as compared to STZ treated animal. There was an initiation of regenerative structures of the affected organs after 15 days of RE treatment. Histopathological observations clearly differentiate the structural changes in pancreas, liver and kidney of STZ and RE treated group. The presence of calyx [4] arene class of compound may be responsible for its antioxidant and antidiabetic properties by absorbing glucose in vivo.